2010
DOI: 10.1093/jxb/erq052
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the HvCKX1 gene decreases the cytokinin oxidase/dehydrogenase level in barley and leads to higher plant productivity

Abstract: Stable RNA interference-based technology was used to silence the expression of the HvCKX1 gene in barley and the TaCKX1 gene in wheat and triticale. The silencing cassettes containing the fragments of these genes in the sense and antisense orientations were cloned into the pMCG161 binary vector and used for Agrobacterium-based transformation. Out of the five cultivars representing the three studied species, transgenic plants were obtained from one barley cultivar Golden Promise, one wheat cultivar Kontesa, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
161
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(184 citation statements)
references
References 52 publications
20
161
2
1
Order By: Relevance
“…In IL50-7, pathways related to IAA biosynthesis were upregulated. Glycogen and starch biosynthetic and cytokinin degradation pathways were upregulated in flag leaves and could be related to increased grain number and weight observed in the introgression line since earlier reports show that null mutation of cytokinin oxidase leads to yield increase (Ashikari et al 2005;Zalewski et al 2010). Shaggy-like protein kinase, auxin response factor, cytochrome P450, sugar transporter, β-glucanase, jumonji domain containing protein, and Myb factors which were reported to be differentially regulated in transcriptome analysis of brassinosteroid (BR) mutants of Arabidopsis thaliana (Mussig et al 2002;Clouse 2011) were also found to be differentially regulated in our study suggesting the involvement of BR pathway in the increased yield of IL50-7.…”
Section: Discussionmentioning
confidence: 93%
“…In IL50-7, pathways related to IAA biosynthesis were upregulated. Glycogen and starch biosynthetic and cytokinin degradation pathways were upregulated in flag leaves and could be related to increased grain number and weight observed in the introgression line since earlier reports show that null mutation of cytokinin oxidase leads to yield increase (Ashikari et al 2005;Zalewski et al 2010). Shaggy-like protein kinase, auxin response factor, cytochrome P450, sugar transporter, β-glucanase, jumonji domain containing protein, and Myb factors which were reported to be differentially regulated in transcriptome analysis of brassinosteroid (BR) mutants of Arabidopsis thaliana (Mussig et al 2002;Clouse 2011) were also found to be differentially regulated in our study suggesting the involvement of BR pathway in the increased yield of IL50-7.…”
Section: Discussionmentioning
confidence: 93%
“…This caused the formation of an increased number of reproductive organs, leading to enhanced grain production in the rice cultivar Habataki (Ashikari et al 2005). The effects of raising endogenous CK levels by silencing CKXs have also been investigated in barley (Zalewski et al 2010), Arabidopsis (Bartrina et al 2011), and tobacco (Zeng et al 2012). In Arabidopsis, the simultaneous silencing of the genes CKX3 and CKX5 resulted in the formation of more flowers/siliques per plant and more seeds per silique, causing a 55 % increase in seed yield relative to wild-type plants ( Bartrina et al 2011).…”
Section: Degradationmentioning
confidence: 99%
“…Seeds from T 1 plants were evaluated which recorded more than 25 days earlier fl owering and day-length insensitivity as compared to the controls (El-Din et al 2011 ). Zalewski et al ( 2010 ) concentrated on silencing the expression of cytokinin oxidase/dehydrogenase ( HvCKX1 ) applying RNAi-based technology to elucidate the function of the gene in barley. The authors succeeded in generating more than 50 lines from which nearly 80 % displayed signifi cantly reduced CKX activity in bulked samples of their T 1 roots.…”
Section: Plant Productivitymentioning
confidence: 99%
“…A positive relationship between enzyme activity and plant productivity was determined, refl ected as the yield, the number of seeds per plant and 1,000 grain weight. Consequently, decreased CKX activity led to a higher plant yield and root weight (Zalewski et al 2010 ). Furthermore, silencing of HvCKX2 resulted in different phenotypes depending on the transformation method.…”
Section: Plant Productivitymentioning
confidence: 99%